2016
DOI: 10.18632/oncotarget.13783
|View full text |Cite
|
Sign up to set email alerts
|

High salt diet stimulates gut Th17 response and exacerbates TNBS-induced colitis in mice

Abstract: This study focuses on characterizing the effect of a high salt diet (HSD) on intestinal immunity and the risk of inflammatory bowel diseases (IBD). We found that mice on a HSD had an increased frequency of IL-17A producing cells in the intestinal lamina propria (LP) compared to mice on a normal diet (ND). Furthermore, most intestinal IL-17A producing cells were CD4+TCRβ+ cells. A HSD increased the LP T helper 17 (Th17) responses in both the small and large intestines but did not increase the Th17 response of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 39 publications
3
71
0
2
Order By: Relevance
“…IBD has long been recognized as a multi-factor-induced inflammatory disease. HSD is demonstrated to add to the risk by altering the secretion of inflammatory cytokines mediated by innate immune cells, and by stimulating the Th17 and ILC3 response in intestines, but by suppressing the function of Treg cells [5,6,11]. This could be an un-DOI: 10.1159/000493096 derlying mechanism for a bland diet to be considered beneficial for illness rehabilitation and is frequently prescribed to patients with GI disease.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…IBD has long been recognized as a multi-factor-induced inflammatory disease. HSD is demonstrated to add to the risk by altering the secretion of inflammatory cytokines mediated by innate immune cells, and by stimulating the Th17 and ILC3 response in intestines, but by suppressing the function of Treg cells [5,6,11]. This could be an un-DOI: 10.1159/000493096 derlying mechanism for a bland diet to be considered beneficial for illness rehabilitation and is frequently prescribed to patients with GI disease.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing studies concentrate on characterizing the effects of HSD on GI disorders from an immune-based perspective [5,6]. Recent studies showed that HSD exacerbated colitis in mice by affecting the gut microbiota and intestinal immune homeostasis [5,11,26].…”
Section: Hsd and The Gi Disordersmentioning
confidence: 99%
See 3 more Smart Citations